10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
PurposeThis study aimed to understand the experiences of hospital workers who had completed a 7-week digital spiritual and psychological wellbeing program conducted in a hybrid mode.DesignA qualitative descriptive methodology was used in this study.SettingA private hospital in Sydney, Australia.ParticipantsEight participants comprising of health care professionals, chaplains, and ancillary workers. Participants were all employed by the hospital the study was conducted at and were predominantly Christian.InterventionThe Empowered and Purposeful Living (EPL) program is a structured 7-week spiritual and psychological wellbeing intervention designed to enhance participant wellbeing. This program was delivered using a hybrid approach comprising face-to-face sessions accompanied with online self-paced components.MethodFollowing completion of the program, participants were interviewed to gain insights into their experiences. Data were collected through semi structured interviews. Data analysis was guided by Braun and Clarke's six-phase framework. NVivo software was used to assist with coding of interview data.ResultsThree themes emerged from the interview data. These themes were: (1) Influence on spirituality, (2) Impacted wellbeing and self-care, and (3) Overall Program Experiences.ConclusionHybrid spiritual and psychological interventions for hospital workers have the ability to foster self-care and resilience, strengthen spirituality, contribute to meaning-making, and promote holistic wellbeing.